2020
DOI: 10.3390/plants9101264
|View full text |Cite
|
Sign up to set email alerts
|

Improved Porosity of Insect Proof Screens Enhances Quality Aspects of Zucchini Squash without Compromising the Yield

Abstract: In a global climate change environment, assuring optimal growing conditions is a difficult challenge, compromising the food supply for a rapidly rising population. The climatic conditions in the protected environment lead to high temperatures and fast insect development, impacting productivity and vegetables qualitative attributes. Consumers’ interest in healthy food requires sustainable tools to manage biotic and abiotic factors and, from this perspective, anti-insect nets represent an excellent “green” solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
(76 reference statements)
0
10
0
1
Order By: Relevance
“…However, traditional strategies to protect the fruits by using insecticides may pose residual risks to the fruit, the environment and human health ( Devine and Furlong, 2007 ); in addition, application of insecticides may not completely eliminate the insects, possibly due to the development of insect resistance ( Sparks et al, 2020 ), as confirmed by the results of our study ( Figure 1C ). IPNs are suitable tools for insect control ( Formisano et al, 2020a ) and have been widely used on vegetables, melons and fruits ( Chien and Chang, 2019 ; Formisano et al, 2020b ). However, the effects of IPNs on Chinese bayberry fruits have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional strategies to protect the fruits by using insecticides may pose residual risks to the fruit, the environment and human health ( Devine and Furlong, 2007 ); in addition, application of insecticides may not completely eliminate the insects, possibly due to the development of insect resistance ( Sparks et al, 2020 ), as confirmed by the results of our study ( Figure 1C ). IPNs are suitable tools for insect control ( Formisano et al, 2020a ) and have been widely used on vegetables, melons and fruits ( Chien and Chang, 2019 ; Formisano et al, 2020b ). However, the effects of IPNs on Chinese bayberry fruits have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the agro-textile industry has tested and marketed innovative nets with improved airflow, due to thinner threads, without affecting exclusion performance. A recent experiment carried out by Formisano et al [27] investigated the effects of a suboptimal growth environment induced by two 50-mesh nets with different porosities (Biorete ® 50 mesh and Biorete ® 50 mesh AirPlus, Arrigoni S.p.A, Uggiate Trevano, CO, Italy) on the production and quality attributes of Cucurbita pepo L. in controlled growing conditions. The improved porosity of the 50-mesh AirPlus net, due to a thinner HDPE filament (Harlene HT ® , Arrigoni S.p.A, Uggiate Trevano, CO, Italy), resulted in increased quality traits of zucchini squash without compromising yield.…”
Section: Technical Aspects Of Anti-insect Netsmentioning
confidence: 99%
“…Wahid et al [112] reported that the accumulation of anthocyanins caused a decrease in the osmotic leaf potential to maximize the absorption and prevent water loss through transpiration, as well as acting as a UV screen. In a recent trial on zucchinis grown under anti-insect nets, thermal stress increased the contents of hydrophilic and lipophilic antioxidant activity, total phenols, and total ascorbic acid [27]. Camejo et al [94] underlined the photoprotective activity of carotenoids such as xanthophyll and terpenoids such as tocopherol in the stabilization of thylakoid membranes.…”
Section: Biochemical Response To Heat Stress: the Role Of Antioxidantmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the primary goal of the horticultural supply chain was to ensure food security by breeding ‘high yielding’ genotypes, considering quality as something exclusively related to visual attributes such as size, shape, and color [ 1 , 2 , 3 ]. However, a changed socio-economic and cultural context have accelerated the transition to a ‘consumer-oriented’ model, where the consumer is aware and informed about the nutraceutical value of vegetables [ 1 , 4 ]. The irreconcilable contrast between the frenetic rhythms imposed by modern times and the desire for a healthy lifestyle has drawn attention to the importance of a nourishing diet as a lifeline [ 5 ].…”
Section: Introductionmentioning
confidence: 99%